Lessons From The Mongolia’s Millennium Development Goal-9, and Its Achievement, Opportunities - Khatanbold, O (Mongolian Journal of International Affairs, 2013)
The paper contains the outputs, conclusions and recommendations of the “Support to Achieving the MDG-9, Phase II” Project (2009-2011). It has shown that reflect two interrelated activities aimed at contributing to a better quality of Mongolia’s democratic governance and describes the process of detailed account of the Project activities that have resulted in the first ever set of institutionalized and fully nationally owned democratic governance indicators in support of human rights, democratic governance and zero tolerance to corruption. The MDG-9 Project believes that the experiences shared the benefit a wide range of audiences, including international organizations and other countries that are interested in developing governance indicators and institutionalizing monitoring mechanisms. It also will be of use to the Mongolian public – both government and civil society for awareness-raising and policy action. Those mentioned descriptions and optional explanations have been categorized on the substantial narrative reports of the project implementation and background of extended activities in the last period of 2009-2011. DOI: http://dx.doi.org/10.5564/mjia.v0i18.67 Mongolian Journal of International Affairs No.18 2013: 16-29